2016
DOI: 10.2147/ott.s116387
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate induces DNA damage and inhibits homologous recombination repair in choriocarcinoma cells

Abstract: ObjectiveThe objective of this study was to investigate the mechanism of sensitivity to methotrexate (MTX) in human choriocarcinoma cells regarding DNA damage response.MethodsTwo choriocarcinoma cancer cell lines, JAR and JEG-3, were utilized in this study. An MTX-sensitive osteosarcoma cell line MG63, an MTX-resistant epithelial ovarian cancer cell line A2780 and an MTX-resistant cervical adenocarcinoma cell line Hela served as controls. Cell viability assay was carried out to assess MTX sensitivity of cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…DHFR catalyzes the reduction of dihydrofolate to tetrahydrofolate, which is indispensable for DNA synthesis. There is also evidence that MTX causes DNA damage in cancer cells, such as oxidative damage and DSBs [46]. Previously, we have shown that MTX induces DNA lesions (DSBs) and senescence in colon cancer cells [47].…”
Section: Discussionmentioning
confidence: 81%
“…DHFR catalyzes the reduction of dihydrofolate to tetrahydrofolate, which is indispensable for DNA synthesis. There is also evidence that MTX causes DNA damage in cancer cells, such as oxidative damage and DSBs [46]. Previously, we have shown that MTX induces DNA lesions (DSBs) and senescence in colon cancer cells [47].…”
Section: Discussionmentioning
confidence: 81%
“…Methotrexate, the third component of the most common chemococktails, is an anti-metabolite folate analog that interferes with the synthesis of purine and pyrimidine bases and, therefore, DNA and RNA synthesis. Of note, the anticancer effect of methotrexate has also been reported to be due to DNA breakage [37]. Thus, it seems that the DNA damage response (DDR) might be the Achilles heel of osteosarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…32) In addition, research has shown that PCNA participate in DNA replication. 33) Therefore, the increase of PCNA synthesis may initiate the reproduction of DNA, resulting in cell growth. The result of our study suggested that PTE decreased the expression level of PCNA, indicating that PTE inhibited the reproduction of DNA, ultimately leading to the inhibition of proliferation in RCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were observed in colon cancer cells treated with inhibitors of thymidylate synthase and in imatinib-resistant chronic myeloid leukemia cells. 34) Rad51 has become a potential anti-tumor target for chemotherapy. Our study showed that PTE decreased Rad51 in RCC cells, demonstrating that PTE-induced inhibition on Rad51 may result in failure of repaired DNA double strand breaks, contributing to the growth retardation in RCC cells.…”
Section: Discussionmentioning
confidence: 99%